2017
DOI: 10.1038/srep40552
|View full text |Cite
|
Sign up to set email alerts
|

18F-FLT and 18F-FDG PET/CT in Predicting Response to Chemoradiotherapy in Nasopharyngeal Carcinoma: Preliminary Results

Abstract: The purpose of this study was to explore the feasibility of 18F-Fluorothymidine (18F-FLT) and 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in predicting treatment response of nasopharyngeal carcinoma (NPC). Patients with NPC of Stage II-IVB were prospectively enrolled, receiving 2 cycles of neoadjuvant chemotherapy (NACT), followed by concurrent chemoradiotherapy. Each patient underwent pretreatment and post-NACT FLT PET/CT and FDG PET/CT. Standard uptake values (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In this study, we found that the SUVmax and SUV min of 18 F-FLT PET/CT are significantly lower than the SUV max and SUV min of 18 F-FDG PET/CT, which is consistent with the results of previous studies (Table 1) [43]. These finding are in line with the results by study conducted by Shi et al (2017) who used the 78% approach for GTV delineation potential to predict tumor regression in NPC patients [21]. The preliminary results of that group reported that parameters of both FDG and FLT PET had medium to strong correlation with NPC tumor response after chemo-radiotherapy; thus this finding avoids the problem of incongruent imaging of tumor motion [21] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that the SUVmax and SUV min of 18 F-FLT PET/CT are significantly lower than the SUV max and SUV min of 18 F-FDG PET/CT, which is consistent with the results of previous studies (Table 1) [43]. These finding are in line with the results by study conducted by Shi et al (2017) who used the 78% approach for GTV delineation potential to predict tumor regression in NPC patients [21]. The preliminary results of that group reported that parameters of both FDG and FLT PET had medium to strong correlation with NPC tumor response after chemo-radiotherapy; thus this finding avoids the problem of incongruent imaging of tumor motion [21] .…”
Section: Discussionsupporting
confidence: 92%
“…Recent articles indicate that high doses modalities imaging and irradiation techniques are required to achieve optimal levels of tumor control in individual patients [20]. Among many clinical diagnosis and assisting tumor staging methods, 18 F-FDG PET/CT and 18 F-FLT PET/CT are the most acceptable and non-invasive procedures for the NPC staging and diagnosis [21]. Despite many technological advances, the target GTVs delineation of 18 F-FDG PET/CT and 18 F-FLT PET/CT in NPC are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…FLT-PET has been used to predict the outcomes of various malignancies, including head and neck cancers treated by radiotherapy 23 , 27 - 34 . The prognostic value of FLT-PET in head and neck squamous cell carcinoma (HNSCC) was demonstrated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among those studies on HNSCC, only 3 NPC patients were included. Recently, a study of 22 patients with primary NPC was conducted to assess the role of FLT-PET in monitoring treatment response 34 . The authors suggested that FLT-PET/CT performed before and after induction chemotherapy prior to chemoradiotherapy might play a role in monitoring the tumor regression; however, its prognostic value was not examined because of the limited sample size and absence of recurrence or death due to the well prognosis of primary NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because of the influence of the partial volume effect (PVE), tumor boundaries on PET images are blurred and the exact size of a tumor cannot be defined precisely. How to determine tumor boundaries and delineate the biologic target of a tumor has been an important focus of research (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Bearing this in mind, we undertook a computer-simulation study on various imaging parameters that might be encountered when conducting imaging with different device performances under various clinical situations.…”
Section: Introductionmentioning
confidence: 99%